Clinical Characteristics, Diagnosis, and Treatment of Major Coronavirus Outbreaks - Mann, Rupinder; Perisetti, Abhilash; Gajendran, Mahesh; Gandhi, Zainab; Umapathy, Chandraprakash; Goyal, Hemant (Frontiers in Medicine, 2020)
Human coronavirus infections have been known to cause mild respiratory illness. It changed in the last two decades as three global outbreaks by coronaviruses led to significant mortality and morbidity. SARS CoV-1 led to the first epidemic of the 21st century due to coronavirus. SARS COV-1 infection had a broad array of symptoms with respiratory and gastrointestinal as most frequent. The last known case was reported in 2004. Middle East respiratory syndrome coronavirus (MERS-CoV) led to the second outbreak in 2012, and case fatality was much higher than SARS. MERS-CoV has a wide array of clinical presentations from mild, moderate to severe, and some patients end up with acute respiratory distress syndrome (ARDS). The third and recent outbreak by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) started in December 2019, which lead to a global pandemic. Patients with SARS-CoV2 infection can be asymptomatic or have a range of symptoms with fever, cough, and shortness of breath being most common. Reverse transcriptase-Polymerase chain reaction (RT-PCR) is a diagnostic test of choice for SARS CoV-1, MERS-CoV, and SARS CoV-2 infections. This review aims to discuss epidemiological, clinical features, diagnosis, and management of human coronaviruses with a focus on SARS CoV-1, MERS-CoV, and SARS CoV-2 infections.